2022
DOI: 10.1007/s00404-022-06471-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ICSI and conventional IVF in non-male factor patients with less than four oocytes

Abstract: Background: We aimed to analyse our clinical results for a particular subgroup of patients with poor ovarian response (POR) in order to clarify if lower number of oocytes is a drawback for proceeding to C-IVF Materials and methods: In this retrospective study, patient les of all couples (#1733) who underwent oocyte retrieval between January 2017 and December 2019 were reviewed and 191 cases diagnosed with non-male factor infertility in which ≤3 cumulus-oocyte-complexes available for fertilisation were analysed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A retrospective study based on 62,641 stimulated fresh cycles of the POR cohort suggested that the fertilization rate was lower in conventional IVF cycles (16). However, another retrospective study revealed that in patients with ≤ 4 oocytes retrieved, the fertilization rate was better via conventional IVF, whereas implantation rates, live birth rates, and miscarriage rates were similar (15). Despite its debatable e cacy and safety, ICSI has become the most commonly used ART technique worldwide, with broadened indications including low oocyte yield, prior fertilization failure with conventional IVF, and advanced maternal age (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A retrospective study based on 62,641 stimulated fresh cycles of the POR cohort suggested that the fertilization rate was lower in conventional IVF cycles (16). However, another retrospective study revealed that in patients with ≤ 4 oocytes retrieved, the fertilization rate was better via conventional IVF, whereas implantation rates, live birth rates, and miscarriage rates were similar (15). Despite its debatable e cacy and safety, ICSI has become the most commonly used ART technique worldwide, with broadened indications including low oocyte yield, prior fertilization failure with conventional IVF, and advanced maternal age (19).…”
Section: Discussionmentioning
confidence: 99%
“…Unpredictable oocyte damage may be caused by ICSI invasiveness, which has always been a critical point, including damage to the cytoplasm of oocytes caused by the injection needle (26, 27), damage to the metaphase II (MII) spindle caused by inaccurate positioning of the injection needle (28) or DNA damage and chromosomal aberrations caused by inappropriate sperm pretreatment (29,30). A retrospective analysis demonstrated that CPR and LBR with ICSI were signi cantly lower than those with conventional IVF in normozoospermic men (31), whereas some studies found no differences in CPR and LBR for either method of fertilization (15,16). Our results were in line with most previous studies, that is, IR, CPR, and LBR were higher in conventional IVF cycles, independent of the number of oocytes retrieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the authors argued that this result should be interpreted as showing no evident benefit of ICSI over c-IVF in the presence of normal sperm parameters. The most recent retrospective analysis of women with ≤3 oocytes available also concluded that low oocyte number is not an indication to perform ICSI when the sperm parameters are within normal WHO ranges and the decision of the insemination method should be solely based on semen quality [ 62 ]. Indeed, implantation rate, live birth rate and fertilization failure rate were similar when the cycles of n = 77 c-IVF and n = 65 ICSI patients were compared.…”
Section: Conventional Ivf Art Indications and Clinical Situationsmentioning
confidence: 99%